2017
DOI: 10.1016/j.immuni.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Group 1 Innate Lymphoid Cell Lineage Identity Is Determined by a cis-Regulatory Element Marked by a Long Non-coding RNA

Abstract: Summary Commitment to the innate lymphoid cells (ILC) lineage is determined by Id2, a transcriptional regulator that antagonizes T and B cell-specific gene expression programs. Yet how Id2 expression is regulated in each ILC subset remains poorly understood. We identified a cis-regulatory element demarcated by a long non-coding RNA (lncRNA) that controls the function and lineage identity of group 1 ILCs, while being dispensable for early ILC development and homeostasis of ILC2s and ILC3s. The locus encoding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 44 publications
2
64
0
Order By: Relevance
“…Like STAT3, STAT5A and STAT5B are also activated by many cytokines including important hematopoietic factors like erythropoietin (EPO) and CSFs. In lymphocytes, STAT5 drives differentiation of innate lymphoid cells, promotes regulatory cell phenotype (Treg) and Foxp3 expression, and inhibits Th17 and follicular helper T cell differentiation …”
Section: Brief Overview Of the Canonical Jak–stat Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Like STAT3, STAT5A and STAT5B are also activated by many cytokines including important hematopoietic factors like erythropoietin (EPO) and CSFs. In lymphocytes, STAT5 drives differentiation of innate lymphoid cells, promotes regulatory cell phenotype (Treg) and Foxp3 expression, and inhibits Th17 and follicular helper T cell differentiation …”
Section: Brief Overview Of the Canonical Jak–stat Pathwaymentioning
confidence: 99%
“…In lymphocytes, STAT5 drives differentiation of innate lymphoid cells, promotes regulatory cell phenotype (Treg) and Foxp3 expression, and inhibits Th17 and follicular helper T cell differentiation. 10,11…”
Section: Introductionmentioning
confidence: 99%
“…However, it is highly probable that thanks to the rapid advances of “single cell” technology this knowledge gap will be soon filled. In comparison to other STATs, the mechanisms of gene regulation by STAT5 have been more extensively studied and better delineated . Beyond the identification of genes undergoing positive and negative regulation, the analysis of genomic distribution of STAT5 has revealed a widespread DNA binding both in unstimulated and IL‐15‐stimulated NK cells .…”
Section: Molecular Mechanisms Driving Stat‐dependent Gene Expressionmentioning
confidence: 99%
“…Regulation of Id2 gene by STAT5 occurs in mice with a peculiar mechanism involving a cis‐DRE associated with a long noncoding RNA (lncRNA), named Rroid (RNA‐demarcated regulatory region of ID2) . While Rroid is specifically expressed in type 1 ILCs, only the Rroid locus, but not the lncRNA itself, is required for the adequate STAT5 occupancy of the Id2 promoter and transcription of this gene in ILC1.…”
Section: Molecular Mechanisms Driving Stat‐dependent Gene Expressionmentioning
confidence: 99%
“…For example, the histone H2A deubiquitinase MYSM1 promotes NK cell development by maintaining an open chromatin configuration at the Id2 locus and by facilitating the recruitment of Nfil3 to the Id2 promoter . More recently, it was shown that a cis ‐regulatory element in the long non‐coding RNA (lncRNA), RNA demarcated regulatory region of Id2 ( Rroid ), that is located upstream of Id2 critically regulates NK cell identity and homeostasis . Acting through long‐range interactions, Rroid promotes chromatin accessibility and STAT5 recruitment to the Id2 locus, thereby enhancing ID2 expression.…”
Section: Transcription Factors That Regulate Nk Cell Development Andmentioning
confidence: 99%